PRECONCENTRATION AND SEPARATION OF ULTRA-TRACE AMOUNTS OF MERCURY(II) USING ULTRASOUND-ASSISTED CLOUD POINT-MICRO SOLID PHASE EXTRACTION BASED ON MODIFIED SILICA AEROGEL WITH [1-(3,5-DICHOLOROPHENYL)-3(2-ETHOXYPHENYL)] TRIAZENE - Motahar, Shiva; Saber-Tehrani, Mohammad; Aberoomand Azar, Parviz; Tadayon, Fariba (Journal of the Chilean Chemical Society, 2019)
In this study, a separation-preconcentration procedure, ultrasound-assisted cloud point-micro solid phase extraction (USA-CP-MSPE) with modified silica aerogel, was developed for the determination of Hg (II) from water samples- modified silica aerogel (SA) adsorbent coupled with metal chelating ligands of [1-(3,5-dicholorophenyl)-3(2-ethoxyphenyl)] triazene (DCPEPT). The adsorbent was characterized by fourier transform infrared spectra (FTIR) and scanning electron microscope (SEM). Some effective factors that influence the microextraction efficiency were investigated and optimized. Desorption study showed that over 96.25 % of Hg(II) could be desorbed from SA-DCPEPT with 1M KBr solution. The influences of some cations and anions on Hg(II) recoveries were also examined. An enhancement factor of 110 was achieved with 1mL sample. The detection limit for mercury(II) ions was 1.5 ng L−1. This method is a simple, fast, accurate, highly stable and selective method which has successfully been applied to the speciation of mercury in water samples.